An Examination of Muscle Activation and Power Characteristics While Performing the Deadlift Exercise With Straight and Hexagonal Barbells. Issue 5 (May 2016) - Camara, Kevin D.; Coburn, Jared W.; Dunnick, Dustin D.; Brown, Lee E.; Galpin, Andrew J.; Costa, Pablo B.
Abstract : Abstract: Camara, KD, Coburn, JW, Dunnick, DD, Brown, LE, Galpin, AJ, and Costa, PB. An examination of muscle activation and power characteristics while performing the deadlift exercise with straight and hexagonal barbells. J Strength Cond Res 30(5): 1183–1188, 2016—The deadlift exercise is commonly performed to develop strength and power, and to train the lower-body and erector spinae muscle groups. However, little is known about the acute training effects of a hexagonal barbell vs. a straight barbell when performing deadlifts. Therefore, the purpose of this study was to examine the hexagonal barbell in comparison with the straight barbell by analyzing electromyography (EMG) from the vastus lateralis, biceps femoris, and erector spinae, as well as peak force, peak power, and peak velocity using a force plate. Twenty men with deadlifting experience volunteered to participate in the study. All participants completed a 1 repetition maximum (1RM) test with each barbell on 2 separate occasions. Three repetitions at 65 and 85% 1RM were performed with each barbell on a third visit. The results revealed that there was no significant difference for 1RM values between the straight and hexagonal barbells (mean ± SD in kg = 181.4 ± 27.3 vs. 181.1 ± 27.6, respectively) ( p > 0.05). Significantly greater normalized EMG values were found from the vastus lateralis for both the concentric (1.199 ± 0.22) and eccentric (0.879 ± 0.31) phases of the hexagonal-barbell deadlift than those of the straight-barbell deadlift (0.968 ± 0.22 and 0.559 ± 1.26), whereas the straight-barbell deadlift led to significantly greater EMG values from the bicep femoris during the concentric phase (0.835 ± 0.19) and the erector spinae (0.753 ± 0.28) during the eccentric phase than the corresponding values for the hexagonal-barbell deadlift (0.723 ± 0.20 and 0.614 ± 0.21) ( p ⩽ 0.05). In addition, the hexagonal-barbell deadlift demonstrated significantly greater peak force (2, 553.20 ± 371.52 N), peak power (1, 871.15 ± 451.61 W), and peak velocity (0.805 ± 0.165) values than those of the straight-barbell deadlift (2, 509.90 ± 364.95 N, 1, 639.70 ± 361.94 W, and 0.725 ± 0.138 m·s −1, respectively) ( p ⩽ 0.05). These results suggest that the barbells led to different patterns of muscle activation and that the hexagonal barbell may be more effective at developing maximal force, power, and velocity.